The correspondence of the adult romantic attachment between siblings and romantic partners - Kamenov, Željka; Jelić, Margareta (2008)
The aim of the study was to compare the adult romantic attachment of persons grown up in the same family. The prototypic perspective claims that the attachment representations formed in childhood remain stable and have the defining influence on relationships in adulthood. From the revisionist perspective, a person’ s attachment to a particular other could be also a function of the experiences with this particular partner. Dyadic analyses were conducted on young adults, their siblings and their romantic partners, comparing the degree of correspondence of the romantic attachment between siblings in relation to the attachment style of their current romantic partners.
XXIX International Congress of Psychology (20. - 25. 07. 2008. ; Berlin, Njemačka)
Projekt MZOS
Projekt MZOS
ENG